Research of Fault Diagnosis Method of Rolling Bearing based on Improved CEEMDAN-TKEO - Xia Changfeng (Jixie chuandong)
According to the problem of difficult to identify rolling bearing fault,the diagnosis method which based on Improved CEEMDAN and Teager energy operator is put forward. First of all,the fault vibration signal measured by sensor is decomposed by using the method of Improved CEEMDAN and a number of intrinsic mode function（ IMF） is got,and the interference of noise components is weakened and the fault feature is enhanced by this method. Then,the Teager energy operator of the correlation modal signal is calculated and the envelope spectrum analysis is carried out. At last,the fault diagnosis is realized by the frequency components.The experimental results show that the diagnosis method based on the Improved CEEMDAN and Teager energy operator can effectively extract the weak characteristic information of the bearing fault signal. The method has certain practical value.